APPLIED LINGUISTICS AND EDUCATIONAL LINGUISTICS - Santi Andriyani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2016)
People who live in the word know that language is a part of tool to communicate each other in interaction. It  deals with the human need of language that such as culture that must be increased and improved in that life. Language takes a part in human life specially in linguistics, either in educational field ( educational linguistics) or in applied linguistics.It is very important to have a good understanding about the concept of applied linguistics and educational linguistics. Both of them are almost similar but they are actually different. By having knowledge about them, we can differentiate and make relationship between them. So that??s why, here the writers try to make a brief summary about applied linguistics and educational linguistics